Deontic sentences, possible worlds and norms - Woleński, Jan (Revus (Ljubljana), 2018)
This paper introduces a non-linguistic theory of norms. The proposal is motivated jointly by Jorgensen's dilemma and Black's objection to the better-known linguistic theories of norms. The argument is structured as follows. The author starts by defining deontic sentence and deontic system. He then applies Kripke's possible world semantics to the analysis of deontic language, before he presents the above-mentioned motivations for conceiving of norms as non-linguistic entities. One such conception is defended in the second half of the paper, where norms are identified with decisions of some normative authority. The author shows how this notion of norm serves both, an intuitive and a formal analysis of normative regulation. Together with the notion of normative function as its formal counterpart, this notion of norm permits one to explain logical relations between deontic sentences with no need to recur to any special semantics or logic of norms.
Keywords: deontic alternatives; deontic language; deontične alternative; deontični jezik; logic; logika; nauk o normah; nekognitivizem; non-cognitivism; normative function; semantics; semantika; theory of norms